Pemberdayaan Komunitas Adat Terpencil (KAT) Oleh Pemerintah Daerah Kabupaten Bengkalis - Andriyus Andriyus; Ranggi Ade Febrian; Handrisal Handrisal; Dita Fisdian Adni (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
In general, the problem associated with Remote Indigenous Communities is accessibility to public facilities that enable them to transform their lives into a better direction. Lack of accessibility to the outside world which causes Remote Indigenous people to fall into various aspects of life such as poverty, low health levels, education levels and others. The purpose of this study was to analyze the Remote Indigenous Community Empowerment by the Bengkalis Regency Government. The results of this study are useful as information and input from the Bengkalis Regency Government in making policies related to the empowerment of Remote Traditional Communities in the Bengkalis Regency Regional Government. The results of this study indicate that the empowerment of Remote Indigenous Communities carried out by the Bengkalis Regency Government. not running properly because seen from human empowerment, social environment and social protection and advocacy is still limited to providing assistance for facilities and infrastructure, there are no concrete steps to improve the quality of the isolated indigenous community. The existence of barriers to empowerment is the limited budget and not yet open to the community of Remote Indigenous Communities to receive new things.